Interventions to Reduce Burnout Among University Lecturers: A Systematic Literature Review - Beibei Cao; Norlizah Che Hassan; Muhd Khaizer Omar (Behavioral Sciences)
The teaching profession is widely recognized as highly challenging due to its intense workload, emotional demands, and ongoing stressors. This Systematic Literature Review (SLR) aims to identify and evaluate various interventions that have been implemented to address lecturer burnout over the past five years. A thorough review of 21 studies published between 2020 and 2024 was conducted across five major databases: Web of Science, Scopus, PubMed, ERIC, and APA PsycINFO. Relevant search terms were used to explore the effectiveness of different interventions aimed at reducing lecturer burnout. Articles were extracted, reviewed, collated, and thematically analyzed to synthesize the findings. Seven distinct interventions were identified as effective in reducing burnout. The most commonly studied intervention was social support, followed by training programs. Other interventions demonstrating positive results include supportive work environments, Rational Emotive Behavior Therapy (REBT), and psychological capital. Additionally, interventions that balanced work and life conditions, facilitated teaching transitions, helped lecturers reevaluate major work demands, and encouraged the utilization of character strengths were also found to yield beneficial outcomes. The implementation of targeted, school-based interventions is crucial for reducing burnout and enhancing the overall well-being of university lecturers. Policymakers, administrators, and educational leaders should prioritize the implementation of school-based awareness and intervention programs.